250 years of promise - H. Holden Thorp (Science, 2026)
America has for its entire history been fascinated with science. Although the lofty ideals associated with establishing the country have mostly to do with personal liberty and equality, the founders were very aware of the importance of new knowledge, and scientific knowledge, in particular. Benjamin Franklin perhaps best exemplified the broad curiosity about both principles of the natural world and the ideals of political philosophy when forging the foundation of a new democracy, and New England was already home to private universities before the Revolution. In the South, public universities were created concomitantly with the formation of the country, first in Georgia and North Carolina, and then in Virginia where Thomas Jefferson devoted his post-presidency to a new institution in Charlottesville. Although these establishments were partly dedicated to training clergy, they were not divorced from science. Jefferson had become an admirer of the chemist Antoine-Laurent Lavoisier while in France and directed the construction of a chemistry laboratory in the basement of the University of Virginia rotunda. At the same time, Elisha Mitchell, a geologist and minister, became president of the University of North Carolina. These universities were revered by America’s founders. President James Madison said that “learned institutions ought to be favored objects with every free people.”